Graphene-MnO2 composite supercapacitor material accomplished tactically using liquid-liquid and solid-liquid interface reaction techniques - Patil, Sagar H.; Gaikwad, Aarti P.; Waghmode, Babasaheb J.; Sathaye, Shivaram D.; Patil, Kashinath R. (New Journal of Chemistry, 2020)
A novel methodology is described to grow architectures of 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite materials to be used in supercapacitors. The in situ growth of the three-dimensional MnO2 fiber-network over the surface of graphene layers is achieved at the solid-liquid interface. The composite electrode shows good electron and charge transfer, rapid plus reversible faradaic reactions and excellent cyclic ability in electrochemical studies. The electrochemical properties of the as-prepared GNS-MnO2/FTO electrode material were assessed by cyclic voltammetry and galvanostatic charge/discharge tests. The specific capacitance of GNS-MnO2 reaches 683 F g(-1) at a current density of 2.2 A g(-1) and shows excellent cycle stability, retaining 96.9% of its initial capacitance up to 5000 cycles. A coulomb efficiency of about 99% displayed by the GNS-MnO2/FTO electrode is an excellent performance for a desired supercapacitor material. Herein, the charge storage mechanism in 3-dimensional graphene nanosheet (GNS)-manganese oxide (MnO2) composite is discussed in detail. Furthermore, at an elevated current density of similar to 10.86 A g(-1), a power density of similar to 6.235 kW kg(-1) is achieved, maintaining an energy density of similar to 7.99 kW h kg(-1); thus, it demonstrates promising potential as an electrode material for supercapacitor application.